The evolution characteristics of diamondoids in coal measures and their potential application in maturity evaluation - Zhai, Jia; Cao, Zhenglin; Fang, Chenchen; Yuan, Yilin; Wu, Wei; Liu, Jinzhong (Frontiers in Earth Science, 2023)
In this study, gold tube thermal simulation experiments were carried out on the soluble components (extracts) and insoluble components (extracted coal-measure mudstones) of coal-measure mudstones, and diamondoid compounds in the pyrolysis products were quantitatively analyzed. The results showed that diamondoid compounds in the extracts and the extracted coal-measure mudstones had undergone the process of formation and decomposition during thermal evolution. Based on the quantitative composition of the extracts and the extracted coal-measure mudstones, the calculated evolution characteristics of the diamondoid compounds in the coal-measure mudstones were mainly consistent with the results of thermal simulation experiments, indicating that the formation of diamondoid compounds was primarily controlled by the original material source. Some diamondoid maturity parameters (MAI, EAI, TMAI-1) in coal-measure mudstones were consistent with the parameters of the evolution characteristics in marine shale. Therefore, the relationship between these parameters and vitrinite reflectance can be established, to calculate the maturity of marine source rocks. In addition, the evolution characteristics and some diamondoid maturity parameters in the extracts and the extracted coal- measure mudstones showed a good linear relationship, but the specific characteristics were different, which may enable the identification of kerogen cracking and secondary cracking of crude oil.